Review Artikel : Pembuatan Tablet Dengan Metode Granulasi Kering - Dewi Rahmawati; Marthy Meliana; Yani Ambari; Ismatun Maulidiyah; Rizki Amalia Putri; Safanda Tiara; Miya Hartini Nur Wakhid; Marselinus Seran; Oktafia Damayanti; Isna Wulan; Brelianty Nevy (CV. ITTC INDONESIA, 2024)
Dry granulation is a method that is carried out by making granules mechanically without the help of a binder. This method has several advantages, including using less equipment, being suitable for active ingredients that are not resistant to heat and humidity and speeding up the tablet disintegration time. The aim of this research is to find out how to make tablet preparations using the dry granulation method. The method used is by reviewing journals from Google Scholar, Pubmed, etc. from 2012-2024. The result of this research is to get the best formulation with various kinds of tests, then we can compare dry granulation and wet granulation, we can optimize the existing formulas.